2022
DOI: 10.3390/ijms23158448
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Extracellular Signal-Regulated Protein Kinase 5 Inhibition in Clear Cell Renal Cell Carcinoma

Abstract: (1) Background: Extracellular signal-regulating kinase 5 (ERK5) has been implicated in many cellular functions, including survival, proliferation, and vascularization. Our objectives were to examine the expression and effect of ERK5 in clear cell renal cell carcinoma (ccRCC). (2) Methods: The expressions of ERK5 and its regulating micro-RNA miR-143 were investigated using immunohistochemistry and quantitative reverse transcriptase PCR in surgical specimens of ccRCC patients. With invitro and in vivo studies, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…In the context of renal tumors, Kanno et al observed that upregulated ERK5 promotes proliferation and suppresses apoptosis in renal cancer cells. The inhibition of ERK5 led to elevated expression of the cyclin-dependent kinase inhibitor p21 and reduced levels of the anti-apoptotic molecule B-cell lymphoma 2 (BCL2) [79]. Arias et al confirmed that increased ERK5 levels foster proliferation, invasion, and metastasis in clear cell renal cell carcinoma, with a positive correlation between ERK5 expression and the disease's invasiveness and metastasis in fresh human samples [81].…”
Section: Kidney and Livermentioning
confidence: 99%
“…In the context of renal tumors, Kanno et al observed that upregulated ERK5 promotes proliferation and suppresses apoptosis in renal cancer cells. The inhibition of ERK5 led to elevated expression of the cyclin-dependent kinase inhibitor p21 and reduced levels of the anti-apoptotic molecule B-cell lymphoma 2 (BCL2) [79]. Arias et al confirmed that increased ERK5 levels foster proliferation, invasion, and metastasis in clear cell renal cell carcinoma, with a positive correlation between ERK5 expression and the disease's invasiveness and metastasis in fresh human samples [81].…”
Section: Kidney and Livermentioning
confidence: 99%
“…The tumors were fixed in 10% buffered formalin, embedded in paraffin, and the samples were coded. Paraffin sections were routinely stained with hematoxylin and eosin, and a pathological diagnosis was made as previously described [21]. Pathological evaluation was performed according to the 2016 World Health Organization classification [22] and the 2017 American Joint Committee on Cancer Tumor-Node Metastasis staging system.…”
Section: Patientsmentioning
confidence: 99%
“…Another study delves into the prognostic implications of ERK5 in various cancers, including lung, prostate, and renal clear-cell carcinomas [ 4 ]. A higher ERK5 expression was correlated with a poorer prognosis in renal carcinoma patients.…”
mentioning
confidence: 99%